HUBUNGAN ANTARA SUPERVISI KEPALA RUANGAN DENGAN KEPATUHAN PERAWAT PELAKSANA DALAM PELAKSANAAN STANDAR PROSEDUR OPERASIONAL RAWAT LUKA POST OPERASI DI RSUD PROF. DR. SOEKANDAR MOJOSARI - Santoso, Windu; Windartik, Emyk (JURNAL KEPERAWATAN SEHAT, 2014)
Supervision is one part of the function carried out by the supervisor guidance to improve the efficiency and effectiveness of staff. Supervision can be done in one invasive post operative wound care is in accordance with the standar operating procedures established by the hospital.The purpose of this research to prove the relationship between supervision by the head of the room with the adherence nurses in implementation of standar operating procedures post operative wound care. The research design was cross sectional. Sample in the study was 31 respondents taken by purposive sampling technique. Method of data collection using questionnaires and observation sheets. The result of the study are using SPSS 16, statistical test produce Spearmen Rank p=0,000<α=0,05 (5%), so H0is rejected it means that there is a significant relationship between supervision head room with adherence nurses in implementation ofstandar operating precedures post operative wound care. Poor supervision can lead to the majority of nurses felt less competent from head of the room, so that most of the nurses were also less adherent in the implementation of standar operating procedures post operative wound care. Head of the room is expected to further improve the competencies that should be possessed by a supervisor such as competency of knowledge and skills, so as to improve the nurses adherence in the implementation of standar operating procedures post operative wound care.Keyword :supervision, adherence, standar operating procedures post operative wound care.Windu Santoso